Factors Affecting the Competence of Cocoa Farmers in Central Sulawesi Province - Andri Amaliel Managanta; Sumardjo Sumardjo; Dwi Sadono; Prabowo Tjitropranoto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2019)
Cocoa is a pre-eminent commodity in Indonesia after oil palm and rubber. However, there has not been much improvement in production due to the lack of technological improvement and lack of extension support in increasing the competence of cocoa farmers. This study aims to: (1) analyze the characteristics of cocoa farmers, extension roles, and competence of cocoa farmers, (2) to analyze the effect of farmer characteristics and extension service role on cocoa farmers competency level, (3) analyze the extension approach in improving farmers’ competence. The study was conducted in four districts in Central Sulawesi Province, namely Poso, Sigi, North Morowali and Donggala districts. Cluster random sampling technique was applied with relatively advanced and less developed village clusters in each district. The total research samples were 380. Data were analyzed using Structural Equation Modeling(SEM). The results show that the level of competence of low cocoa farmers is caused by the weakness to cosmopolitan. In addition, the low competence is due to the weak role of extension personal as communicator, advisor, dynamics role, motivator, organizer, and educator. Efforts to increase farmer's competence require their cosmopolitan improvement and extension personal roles as communicators, advisors, motivators, organizers, educators and dynamic role.